Everywhere Taksim: Sowing the Seeds for a New Turkey at Gezi - Toktamis, Kumru F.; David, Isabel (Protest and Social Movements, 2015)
In May 2013, a small group of protesters made camp in Istanbul's Taksim Square, protesting the privatisation of what had long been a vibrant public space. When the police responded to the demonstration with brutality, the protests exploded in size and force, quickly becoming a massive statement of opposition to the Turkish regime. This book assembles a collection of field research, data, theoretical analyses, and cross-country comparisons to show the significance of the protests both within Turkey and throughout the world.